Strategi Pemerintah dalam Penerapan Disiplin Kerja Aparatur Sipil Negara di Daerah Khusus Ibukota Jakarta - Adi Sukrianto; Erni Saharuddin (Universitas Medan Area, 2021)
This research aims to find out the Government's strategy in the application of state civil servant discipline in DKI Jakarta, as well as to get any solutions that can be applied in improving the discipline of the State Civil Apparatus. Using research methods of literature studies drawn from several references to journals, books, laws and other relevant articles that support this research, the Jakarta Provincial Government uses various strategies in an effort to implement the working disciplines of the State Civil Apparatus in accordance with applicable laws and regulations and agreements that have been made. The efforts made by the government is a strategy that can be a solution to improve discipline, some of which are: giving appreciation to employees who have completed their tasks appropriately and quickly, giving punishment or sanctions to employees who make mistakes, explaining and providing understanding of the unknown to eliminate lack of confidence, increase skills and potential.